The impact of low-dose carcinogens and environmental disruptors on tissue invasion and metastasis - Ochieng, Josiah; Nangami, Gladys N.; Ogunkua, Olugbemiga; Miousse, Isabelle R.; Koturbash, Igor; Marah, Valerie Odero; McCawley, Lisa J.; Makker, Pratima Nangie; Ahmed, Nuzhat; Luqmani, Yunus; Zhenbang, Chen; Papagerakis, Silvana; et al. (Oxford University Press, 2015)
The purpose of this review is to stimulate new ideas regarding low-dose environmental mixtures and carcinogens and their potential to promote invasion and metastasis. Whereas a number of chapters in this review are devoted to the role of low-dose environmental mixtures and carcinogens in the promotion of invasion and metastasis in specific tumors such as breast and prostate, the overarching theme is the role of low-dose carcinogens in the progression of cancer stem cells. It is becoming clearer that cancer stem cells in a tumor are the ones that assume invasive properties and colonize distant organs. Therefore, low-dose contaminants that trigger epithelial-mesenchymal transition, for example, in these cells are of particular interest in this review. This we hope will lead to the collaboration between scientists who have dedicated their professional life to the study of carcinogens and those whose interests are exclusively in the arena of tissue invasion and metastasis.